Development of a rotary push-cut-type negative-pressure-airflow end-effector for harvesting safflower filaments - Zhang, Zhenguo; Xing, Zhenyu; Zhao, Minyi; Xu, Peng; Guo, Quanfeng; Zeng, Chao; Shi, Ruimeng; Wang, Yunze (International Journal of Agricultural and Biological Engineering, 2025)
Safflower is one of the most important oil crops worldwide. To improve the efficiency and quality of harvesting soft safflower filaments, minimize filament damage by the blade, and ensure the integrity of the filaments, an end-effector with a rotary push-cut-type negative-pressure airflow was designed. The design of the rotary blade edge curve was based on Archimedean and logarithmic spirals. The effect of the Archimedean spiral on the pushing of the scattered filaments was investigated. The rotary-cutting force and speed of the logarithmic helix on the soft filaments were analyzed. The sliding cut angle and feed speed of the blade are the key factors governing filament removal and damage. A simulation model of the cutting chamber flow field was established for the change in airflow with the position and speed rotation of the blade, allowing analysis of the parameters of the negative-pressure airflow. Single-factor and Box-Behnken tests were performed with the sliding cut angle, blade feed speed, and negative-pressure airflow speed as influencing factors and filament removal, damage, and drop rate as indices. The response surface clarified the effects of various factors on these indices. Optimal parameters were a sliding cut angle of 32.20°, a blade feeding speed of 0.031 m/s, and a negative-pressure airflow speed of 4.57 m/s. The corresponding filament removal, damage, and drop rates were 93.47%, 6.94%, and 4.33%, respectively. Optimization results showed that filament removal, damage, and drop rates were 93.50%, 7.02%, and 4.43%, respectively. The harvesting process met the requirements of high efficiency and low damage. Keywords: harvesting, safflower filaments, end-effector, rotary push-cut type, negative-pressure airflowDOI: 10.25165/j.ijabe.20251803.9722Citation: Zhang Z G, Xing Z Y, Zhao M Y, Xu P, Guo Q F, Zeng C, et al. Development of a rotary push-cut-type negativepressure-airflow end-effector for harvesting safflower filaments. Int J Agric & Biol Eng, 2025; 18(3): 82–96.